In vitro screening of Annonareticulata L. pericarp for antimicrobial activity - V.S.SANGEETHA; BEENA LAWRENCE (International Journal of Pharma and Bio Sciences, 2017)
Unripe and ripe pericarp extracts of Annona reticulata Linn. fruits were investigated for their in vitro antimicrobial properties against three gram-positive bacteria (Bacillus subtilis, Enterococcus faecalis and Staphylococcus aureus), gram-negative bacteria (Eschericia coli, Pseudomonas aeruginosa and Proteus vulgaris) and three fungal strains (Aspergillus flavus, Aspergillus niger and Penicillium chrysogenum). All the extracts showed activity against at least one strain of bacteria and fungi and the result shows there is significant differences (P<0.05) between the activities of extract on microorganism. The ethanol extract of unripe pericarp exhibited the highest inhibition activity against the growth of Eschericia coli (19.67 mm) which was higher than the zone of inhibition produced by Ampicillin standard (15.33 mm). Also MIC for ethanol extract was the lowest (1.0 mg/ml) compared with other extracts. From the investigation carried out it was seen that the ethanolic extract of unripe pericarp could be a possible source of obtaining new and effective herbal medicines to treat infections.